Test-item type preferences of college algebra teachers - Angeles, Rosendo Guanlao 1961 (1988)
The content of the tests were evaluated based on the ability levels of students; the presentation, based on selected characteristics. It was concluded that College Algebra teachers preferred number problems, word problems, multiple choice, illustrations/sketches, and identification test-item types the most. Frequently during final examinations and quizzes, number problems ranked the highest, followed by multiple choice in quizzes and word problems in final examination. The weights given per correct answers were based on the thinking processes involved and the amount of time it takes to arrive at an answer. College Algebra teachers tend to use methods which reinforce developing skills in computation and recall rather than high cognitive skills and processes.
"June 1988."
Vita.
Thesis (M.A. Mathematics)--University of the Philippines, Diliman.
Keywords: Mathematics teachers -- Philippines; College teachers -- Philippines